Heterostructures of photonic crystals: Frequency bands and transmission coefficients - N. Stefanou; V. Yannopapas; A. Modinos (Computer Physics Communications, 1998)
We present a program for the calculation of the frequency band structure of an infinite photonic crystal, and of the transmission, reflection and absorption coefficients of light by a slab of this crystal. The crystal consists of a stack of identical slices parallel to a given surface; a slice may consist of a number of different components, each of which can be either a homogeneous plate or a multilayer of spherical particles of given periodicity parallel to the surface.